2022
DOI: 10.3390/jcm11247522
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Severity of Community- and Hospital-Acquired Hyponatremia in Pediatrics

Abstract: Hyponatremia is the most common electrolyte disturbance in hospitalized children, with a reported incidence of 15–30%, but its overall incidence and severity are not well known. The objective of our study was to determine the incidence, severity, and associated risk factors of community- and hospital-acquired hyponatremia on a general pediatric ward. Data of 5550 children admitted from June 2012 to December 2019 on plasma sodium and discharge diagnosis were analyzed by logistic regression model. Clinically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A recent study reported a 4.3% prevalence of neonatal hyponatremia, predominantly in preterm neonates within hospital settings ( Storey et al, 2019 ). However, in a study analyzing 5,550 pediatric admissions, the incidence of community-acquired hyponatremia was found to be more common (15.8%) than hospital-acquired (1.4%), with the majority of cases being mild to moderate in severity and severe instances being notably rare ( Rius-Peris et al, 2022 ). The etiological spectrum of neonatal hyponatremia is diverse, including iatrogenic factors, abnormalities in the renal mineralocorticoid pathway, inappropriate antidiuretic hormone secretion (SIADH), acute renal failure, heart failure, and gastrointestinal conditions such as gastroenteritis ( Mazzoni et al, 2019 ), congenital chloride diarrhea ( Wedenoja et al, 2010 ; Cendal et al, 2021 ), and necrotizing enterocolitis (NEC) ( Palleri et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a 4.3% prevalence of neonatal hyponatremia, predominantly in preterm neonates within hospital settings ( Storey et al, 2019 ). However, in a study analyzing 5,550 pediatric admissions, the incidence of community-acquired hyponatremia was found to be more common (15.8%) than hospital-acquired (1.4%), with the majority of cases being mild to moderate in severity and severe instances being notably rare ( Rius-Peris et al, 2022 ). The etiological spectrum of neonatal hyponatremia is diverse, including iatrogenic factors, abnormalities in the renal mineralocorticoid pathway, inappropriate antidiuretic hormone secretion (SIADH), acute renal failure, heart failure, and gastrointestinal conditions such as gastroenteritis ( Mazzoni et al, 2019 ), congenital chloride diarrhea ( Wedenoja et al, 2010 ; Cendal et al, 2021 ), and necrotizing enterocolitis (NEC) ( Palleri et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%